2016
DOI: 10.1007/s00170-016-9006-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of predeformation on microstructure evolution of superplastically formed Al 5083 alloy

Abstract: Cavitation is the main defect encountered during superplastic forming (SPF) of thin sheet aluminum alloys. In the present paper, the influence of preforming operation (cold or hot) on the superplastic forming ability and quality of 1.6-mm-thick sheet of 5083 SPF aluminum alloy is investigated. Specifically, grain size evolution and the characteristics of the cavitation process are discussed as a function of prior deformation and the preforming temperature. Optical and field emission gun scanning electron micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Loucif et al attained maximum elongation up to 400% at 350 • C and 10 −1 s −2 while Caballero et al obtained a maximum elongation of 126% at the same temperature and strain rate. In another experiment, Chentouf et al [93] analyzed the superplastic behavior of AA5083 by hot and cold preform, whose average grain size was determined to be 8.32 and 7.95 µm respectively. They concluded that the number of cavities in the hot preform case were less than in the cold preform case and hot preformed samples led to an increase in the nucleation of subsurface discontinuities.…”
Section: Effect Of Microstructure Refinement Techniques On the Superpmentioning
confidence: 99%
“…Loucif et al attained maximum elongation up to 400% at 350 • C and 10 −1 s −2 while Caballero et al obtained a maximum elongation of 126% at the same temperature and strain rate. In another experiment, Chentouf et al [93] analyzed the superplastic behavior of AA5083 by hot and cold preform, whose average grain size was determined to be 8.32 and 7.95 µm respectively. They concluded that the number of cavities in the hot preform case were less than in the cold preform case and hot preformed samples led to an increase in the nucleation of subsurface discontinuities.…”
Section: Effect Of Microstructure Refinement Techniques On the Superpmentioning
confidence: 99%
“…It is well known that recrystallized grains are formed at specific nucleation sites such as initial grain boundaries, cube bands, transition bands, shear bands and deformation zones around preexisting second phase particles [12]. In this study, the grains refined from 31.8μm to 9.4μm, due to the large deformation of the cold deformation, leading to dislocation congestion and its density increased, offered more nucleation sites and higher stored energy [9,13]. Tensile Properties.…”
Section: Resultsmentioning
confidence: 85%
“…The rapid superplastic forming process is divided into four steps: Alloy heating, pre-forming, blow forming, and heat treatment. The process of the whole production is shown in Figure 2 [ 12 , 13 ].…”
Section: Aluminum Alloy Rail Vehicle Side Window Forming Designmentioning
confidence: 99%